2017
DOI: 10.5194/angeo-35-629-2017
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic activity and local time dependence of the distribution of ultra low-frequency wave power in azimuthal wavenumbers, <i>m</i>

Abstract: Abstract. The azimuthal wavenumber m of ultra lowfrequency (ULF) waves in the magnetosphere is a required parameter in the calculations of the diffusion rates of energetic electrons and protons in the magnetosphere, as electrons and protons of drift frequency ω d have been shown to radially diffuse due to resonant interaction with ULF waves of frequency ω = mω d . However, there are difficulties in estimating m, due to lack of multipoint measurements. In this paper we use magnetic field measurements at geosync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…For example, through ionospheric radar observations, Fenrich et al () found that m > 17 ULF waves are concentrated in the midnight and local afternoon, while m < 17 waves are concentrated near the flank regions. Similarly, Sarris and Li () found that the mode number values of Pc5 ULF waves are generally higher at the nightside than the dayside. Therefore, assuming a uniform mode structure around the Earth in radial diffusion calculations, rather than using a realistic local time distribution of the mode number, can lead to significant uncertainty in D LL estimation where the local time dependent mode structure needs to be properly drift averaged.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…For example, through ionospheric radar observations, Fenrich et al () found that m > 17 ULF waves are concentrated in the midnight and local afternoon, while m < 17 waves are concentrated near the flank regions. Similarly, Sarris and Li () found that the mode number values of Pc5 ULF waves are generally higher at the nightside than the dayside. Therefore, assuming a uniform mode structure around the Earth in radial diffusion calculations, rather than using a realistic local time distribution of the mode number, can lead to significant uncertainty in D LL estimation where the local time dependent mode structure needs to be properly drift averaged.…”
Section: Introductionmentioning
confidence: 78%
“…Despite its crucial importance, physical quantification of the azimuthal mode number of ULF waves is difficult and has been a missing part in the calculation of the radial diffusion coefficients (e.g., Tu et al, ; Sarris, ; Sarris & Li, ). In principle, to determine the mode structure of a simple harmonic wave at a given frequency up to mode number m max , we need at least 2 m max equally spaced azimuthal coherent field measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that ULF waves with a global scale are highly efficient at accelerating ultrarelativistic electrons in the outer belt. ULF waves (essentially the compressional mode or compressional poloidal mode) with an azimuthal wave number of 1 have also been found to be the dominant component by both multispacecraft observations (Sarris & Li, ) and magnetohydrodynamic simulation studies (Tu et al, ). Within the time scale of an hour, flux enhancement of an order of magnitude can be achieved with the presence of such waves at SSC.…”
Section: Discussionmentioning
confidence: 99%
“…However, in practice, this is often simplified by assuming m = 1. Sarris and Li () found that the amplitude of power is indeed concentrated in low m numbers for the dayside and for less geomagnetically active time periods but less so for the nightside and geomagnetically active periods. Murphy et al () found that the m number during a moderate storm is typically low but the distribution of positive or negative values depends on radial location; this initial study gives some idea how the direction of propagation (i.e., m < vs. >0) is distributed among ULF waves but due to challenges in measuring m much more work is required.…”
Section: Other Sources Of Uncertainty In Radial Diffusion Coefficientsmentioning
confidence: 99%